2020
DOI: 10.1038/s41598-020-62912-0
|View full text |Cite|
|
Sign up to set email alerts
|

CXXC5 as an unmethylated CpG dinucleotide binding protein contributes to estrogen-mediated cellular proliferation

Abstract: Evidence suggests that the CXXC type zinc finger (ZF-CXXC) protein 5 (CXXC5) is a critical regulator/integrator of various signaling pathways that include the estrogen (E2)-estrogen receptor α (ERα). Due to its ZF-CXXC domain, CXXC5 is considered to be a member of the ZF-CXXC family, which binds to unmethylated CpG dinucleotides of DNA and through enzymatic activities for DNA methylation and/or chromatin modifications generates a chromatin state critical for gene expressions. Structural/functional features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…We thus propose a mechanism that regulates this binding via the concurrent demethylation of a CpG island in the PPR of CXXC5 and upregulation of ESR1 in luminal-subtype cancers -illustrating a case study of a DNAm priming event present in aged epithelia that creates an opportunity for cancer subtype-specific regulation. Indeed, CXXC5 was shown to participate in E2-driven cellular proliferation through its modulatory effect on the expression of other genes also regulated by E2 [Ayaz et al, 2020]. CXXC5 overexpression, which we establish to be anti-correlated with DNAm at specific CpGs, is associated with poor prognosis of ER+ breast cancers [Ayaz et al, 2020].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We thus propose a mechanism that regulates this binding via the concurrent demethylation of a CpG island in the PPR of CXXC5 and upregulation of ESR1 in luminal-subtype cancers -illustrating a case study of a DNAm priming event present in aged epithelia that creates an opportunity for cancer subtype-specific regulation. Indeed, CXXC5 was shown to participate in E2-driven cellular proliferation through its modulatory effect on the expression of other genes also regulated by E2 [Ayaz et al, 2020]. CXXC5 overexpression, which we establish to be anti-correlated with DNAm at specific CpGs, is associated with poor prognosis of ER+ breast cancers [Ayaz et al, 2020].…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, CXXC5 was shown to participate in E2-driven cellular proliferation through its modulatory effect on the expression of other genes also regulated by E2 [Ayaz et al, 2020]. CXXC5 overexpression, which we establish to be anti-correlated with DNAm at specific CpGs, is associated with poor prognosis of ER+ breast cancers [Ayaz et al, 2020]. Because CXXC5 binds unmethylated CpG dinucleotides, upregulation of CXXC5 in luminal-subtype cancers could lead to increased positive (self-)regulation by TFs by preventing methylation of CXXC5-occupied promoter regions.…”
Section: Discussionmentioning
confidence: 99%
“…Another critical regulator of various signaling pathways, the CXXC type zink finger protein 5 (CXXC5) is suggested to act as a transcription factor as well as an epigenetic modifier [54]. It is highly expressed in mouse and human pDCs, where, as an epigenetic regulator it controls DNA methylation and histone modifications [55].…”
Section: Transcription Factorsmentioning
confidence: 99%
“…CXXC5 is located on chromosome 5q31.2 and encodes a 322 amino-acid protein with a predicted molecular mass of 33 kDa 8 , 10 . Retinoic acid 11 , transforming growth factor-β 12 , bone morphogenetic protein 4 13 , 14 , Wnt3a 15 17 , and estrogen 18 21 modulate the expression of CXXC5 in experimental systems. The encoded CXXC5 protein alters gene expressions 13 , 17 , 21 27 that result in the modulation of diverse cellular events, including signal transduction, DNA damage response, metabolism, proliferation, differentiation, and death 11 13 , 15 , 21 , 22 , 24 , 25 , 27 30 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanism by which CXXC5 regulates gene expressions remains unclear. We recently showed that CXXC5 is an unmethylated CpG binder but lacks an intrinsic transcription regulatory function 21 . This raises the possibility that CXXC5 acts as a nucleation factor to establish a transcription state restrictive or permissive for transcription by interacting with transcription factors, transcription co-regulatory proteins, histone, and/or DNA modifiers.…”
Section: Introductionmentioning
confidence: 99%